2017
DOI: 10.17576/pengurusan-2017-51-09
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Retaliation to Halal Violation Incidents: The Mediating Role of Trust Recovery

Abstract: In recent years, there have been several cases in which Halal certification has been rescinded by the authorized institutions due to negligence to adhere to the certify standards of Halal products. The purpose of this study is to explore the influence of severity of Halal violation on consumer anti-consumption behaviors through the mediating role of trust recovery. A survey design using cross-sectional primary data from 212 Malaysian consumers that were aware and/or had experienced the violation of a Halal cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A study conducted in the USA revealed that more than 80 percent of Muslim consumers believe that preferring permissible meat is very important (Ibrahim et al, 2008). Muslims believe that halal meat is healthy, and violation of halal production methods is a significant factor in food anti-consumption (Bonne et al, 2009;Omar et al, 2017).…”
Section: Literature Review Consumption and Anti-consumption Of Meatmentioning
confidence: 99%
“…A study conducted in the USA revealed that more than 80 percent of Muslim consumers believe that preferring permissible meat is very important (Ibrahim et al, 2008). Muslims believe that halal meat is healthy, and violation of halal production methods is a significant factor in food anti-consumption (Bonne et al, 2009;Omar et al, 2017).…”
Section: Literature Review Consumption and Anti-consumption Of Meatmentioning
confidence: 99%
“…In their study, organizational trust was found to be significant in affecting individual behavior in the workplace. Furthermore, 'trust' is well-known in the context of marketing, especially its role as a mediating variable between the dependent and independent variables, as documented in several recent studies (Mabkhot et al 2017;Maulod et al 2020;Omar et al 2017).…”
Section: Trend Topicsmentioning
confidence: 95%
“…Researchers in the field of food technology have used MNDT to identify fruit states and assess their freshness [21]. In other studies, liquids like oil and animal fats have been characterized using the MNDT [22], [23]. In the MNDT analysis of animal fats, the researchers look at the S-parameters of the raw and baked fats without using correlation analysis [23].…”
Section: Introductionmentioning
confidence: 99%